PENGARUH MOTIVASI BERPRESTASI DAN KOMPETENSI TERHADAP KINERJA APARATUR PENGAWASAN INTERN PEMERINTAH PADA INSPEKTORAT KABUPATEN PONOROGO - Yuliana, Fitri Eko; Suddin, Alwi; Suprayitno, Suprayitno (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The purpose of this study is to determine the effect of achievement motivation and competence on the performance of the Government Internal Oversight Apparatus (APIP) in the Ponorogo Regency Inspectorate. This research uses a quantitative approach. Sampling in this study used a sampling technique using saturated sampling, where all employees at the Inspectorate of Ponorogo Regency, amounting to 40 employees, were subjected to this study. Data collection techniques using questionnaires and documentation. Data analysis techniques using classical assumption test techniques, path analysis, hypothesis testing, F test and coefficient of determination test. From the results of the regression calculations performed, the results showed that based on multiple linear regression calculations showed achievement motivation and competence affected the performance of the Government Internal Supervisory Apparatus (APIP) in the Ponorogo Regency Inspectorate and while based on the t test showed that achievement motivation had no significant effect on performance and competence has a significant effect on the performance of the Government Internal Oversight Apparatus (APIP) in the Ponorogo Regency Inspectorate.